Improving Community Skills in Making Batik Jumputan Through Training PKK Mothers at Sumbergempol, Kabupaten Tulungagung - Siti Imroatul Maslikah; Murni Saptasari; Sitoresmi Prabaningtyas; Srirahayu Lestari; Agung Witjoro; Mimien Henie Irawati; Susriyati Mahanal; Dyah Ayu Eka Fitriana; Muhammad Athoillah; Yuslinda Anisa; Siti Nur Arifah; Alif Rofiqotun Nurul Alimah (Future Science, 2019)
The purpose of this study is to improve the community’ skills of making batik jumputan through training of 21 PKK mothers at Sumbergempol District, Tulungagung Regency. This type of research is descriptive qualitative. Participants involved in this study were selected randomly (random sampling technique). Data collection techniques in the form of skills test making batik jumputan (paper based-test) conducted before and after training. Data analysis was performed using the calculation and categorization of N-Gain. The results showed that the training in making batik jumputan could improve the skills of PKK mothers at Sumbergempol District, Tulungagung Regency in the moderate (62%) and high (38%) categories.